Notes about the corps in Frantz Fanon: the anti-blackness racism epidermization - Oliveira, Glauber Franco de (2024)
Particularly known for his writings on the issue of colonialism and its implications for peripheral populations, especially for black people, Frantz Fanon left a legacy as a work that already denounced the ills that imperialism had engendered for an entire population. From studies on the psychological dimension of the subject assimilated by whiteness, passing through writings on the clinical issue and arriving at the critique of colonialism in the political, economic and subjective spheres, his work permeates a series of contemporary discussions, from which we highlight the problem of racism as a different marker. However, an issue that is addressed by the author, but still little explored in literature, concerns the corporeal dimension of racism, in particular the understanding of the body in Fanon's text. The naturalized black body was already crossed in reality by the manichaeisms of white and black, superior and inferior and many others created by narcissistic eurocentrism since the consolidation of the practice of racial and colonial violence endowed with their own logic. With that in mind, this is an article that aims to bring notes on the body in Fanonian studies, an original critic of this state of affairs. In a nutshell, what is the body in Fanon? What is the dimension of corporeality for the realization of the subject in society in view of what is apprehended from his body? In the meantime, the hypothesis is proposed that Fanon has two distinct levels in his argumentative development: the manichaean description and the radical humanism. For that, a bibliographical research of Fanon's consolidated works and the specialized literature about him was carried out.